(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2025)
This study examines the participation and budget distribution system in Baitul Mal during the time of Prophet Muhammad, focusing on how public funds were allocated and managed. The research addresses questions regarding the mechanisms of budgeting, the involvement of the community in financial oversight, and the principles guiding the fair distribution of wealth to different social groups. Using a literature study method, the study analyzes historical records, Islamic sources, and previous research to obtain comprehensive insights into Baitul Mal’s operations. The findings indicate that Baitul Mal implemented a transparent, participatory, and justice-oriented budgeting system, which ensured the welfare of the poor, supported public projects, and fostered social solidarity among Muslims. Community involvement not only strengthened accountability but also nurtured moral and social values within the society. The study concludes that the Baitul Mal system provides an exemplary model of ethical, equitable, and sustainable economic management in Islam, which remains relevant for contemporary financial governance.